The role of anions on the Helmholtz Plane for the solid-liquid interface in aqueous rechargeable lithium batteries. (August 2020) - Hu, Jiangtao; Ren, Wenju; Chen, Xin; Li, Yiwei; Huang, Weiyuan; Yang, Kai; Yang, Luyi; Lin, Yuan; Zheng, Jiaxin; Pan, Feng
Abstract: The Li-ion transport at the electrode/electrolyte interface in lithium ion batteries (LIBs) relies on the structure of the electrical double layer. Our previous work indicates that the constructing of Janus amphiphilic coordination interface on LiFePO4 in aqueous electrolyte relieves the energy barriers of the Li + solvation/desolvation process. Here, aqueous electrolytes with different salts (LiNO3, LiCl, Li2 SO4 and CH3 COOLi) were tested in LiFePO4 single nanoparticle, and Ab initio calculations and simulation were carried out. H2 O has a stronger binding energy with Fe and Li on the surface of LiFePO4 to form Janus interface, so the activation energies of Li-ion in Janus layer are the same in the four electrolytes. The simulation result confirms that the Li-ion transport at the interface have a close relationship with the anionic physical characteristics. Combing with the experimental and calculated results, it can be inferred that the activation energy ( E a ) of Li-ion includes Janus interface, anion adsorption layer and cation adsorption layer. Owing to the same Janus interface and cation adsorption layer, the difference of E a in the four kinds of electrolytes must come from the anion adsorption layer in inner Helmholtz plane (IHP). This work provides a guiding significance on development of aqueous electrolyte systems. Graphical abstract: Image 1 Highlights: We firstly explored the effects of anions on surface reconstruction and Helmholtz plane vs Li +  transport at the solid-liquid interface. Ab initio calculations prove that both H2 O and anions can realize interface reconstruction, but H2 O has priority in the real environment. The Li +  interface activation energy calculation includes Janus interface, anion adsorption layer and cation adsorption layer.